The Heat Stress Response and Diabetes: More Room for Mitochondrial Implication - Miova, Biljana; Dimitrovska, Maja; Dinevska-Kjovkarovska, Suzana; V. Esplugues, Juan; Apostolova, Nadezda (Current Pharmaceutical Design, 2016)
Heat preconditioning is a rapid cellular adaptive mechanism shared by many cells/ organs / organisms that results in synthesis and accumulation of heat shock proteins (HSPs), which are responsible for increased tolerance and survival of animals during and after heat stress (HS). HSPs function as molecular chaperones by restoring cellular homeostasis and promoting cell survival, and their major functions include protection of cells from injury by preventing protein damage and aggregation. Abundant evidence points to the ability of one kind of stress caused by external factors that induce primary adaptations in the organism to provide protection against additional stress of the same or another type, a phenomenon known as cross-tolerance. Diabetes mellitus (DM) is one of the diseases which have been associated with increased tissue sensitivity and vulnerability due to incorrect protein folding. Thus, HSPs may play an important role in minimizing the protein damage that can occur under the stressful conditions created by the disease. By increasing HSP production, heat preconditioning may be a promising therapy for patients with lifestylerelated diseases such as hypercholesterolemia, hypertension, DM and obesity. Also, pancreatic β-cells exposed to acute HS activate defence mechanisms which include HSP synthesis and are less sensitive to the effects of cytotoxic agents such as NO, oxygen radicals and -cytotoxic diabetogenic agents, such as streptozotocin (STZ). Mitochondrial dysfunction and mitochondria-specific cell stress are associated and can even be a primary abnormality caused by DMinduced hyperglycaemia and oxidative stress. There are an increasing number of genetic and/or pharmacological modulations of HSPs that have revealed the connection between HSPs, mitochondria and diabetes. HSPs may affect mitochondrial function in multiple ways, but the influence on skeletal muscle and adipose tissue, as well as on the pancreas, has attracted most interest as a key element in the development of novel pharmacological approaches to treating DM and associated metabolic conditions.
Keywords: cross-tolerance